2011
DOI: 10.3389/fendo.2011.00083
|View full text |Cite
|
Sign up to set email alerts
|

Lumiestrone is Photochemically Derived from Estrone and may be Released to the Environment without Detection

Abstract: Endocrine disrupting chemicals are adversely affecting the reproductive health and metabolic status of aquatic vertebrates. Estrone is often the dominant natural estrogen in urban sewage, yet little is known about its environmental fate and biological effects. Increased use of UV-B radiation for effluent treatments, and exposure of effluents to sunlight in holding ponds led us to examine the effects of environmentally relevant levels of UV-B radiation on the photodegradation potential of estrone. Surprisingly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 55 publications
(87 reference statements)
4
27
0
Order By: Relevance
“…The lumiestrone spectrum also shows chemical shifts for protons attached to the C8 (d ¼ 0.9 ppm) and C11 (d ¼ 0.93 ppm) carbon atoms that are significantly different than those for E1. Previous work demonstrates that E1 can be converted to its lumiestrone epimer upon irradiation with UV light under controlled laboratory conditions and when spiked into wastewater and irradiated in sunlight (Butenandt et al, 1941;Johnson and Chinn, 1951;Trudeau et al, 2011). As seen below, our work extends the findings of previous groups by characterizing lumiestrone's photochemical yield, photolability, and estrogenicity.…”
Section: Characterization Of Lumiestronesupporting
confidence: 78%
See 1 more Smart Citation
“…The lumiestrone spectrum also shows chemical shifts for protons attached to the C8 (d ¼ 0.9 ppm) and C11 (d ¼ 0.93 ppm) carbon atoms that are significantly different than those for E1. Previous work demonstrates that E1 can be converted to its lumiestrone epimer upon irradiation with UV light under controlled laboratory conditions and when spiked into wastewater and irradiated in sunlight (Butenandt et al, 1941;Johnson and Chinn, 1951;Trudeau et al, 2011). As seen below, our work extends the findings of previous groups by characterizing lumiestrone's photochemical yield, photolability, and estrogenicity.…”
Section: Characterization Of Lumiestronesupporting
confidence: 78%
“…Indeed, recent studies suggest that photochemical degradation reactions may be important environmental fate processes for estrogenic EDCs (Jü rgens et al, 2002;Coleman et al, 2004;Lin and Reinhard, 2005;Mazellier et al, 2008;Zuo et al, 2006;Atkinson et al, 2011;Trudeau et al, 2011). Two of these studies Trudeau et al, 2011) highlight an important and often neglected aspect of environmental photochemistry: phototransformation products may retain biological activity (Boreen et al, 2003). In their recent work, Trudeau, et al used a human cell line transfected with zebrafish estrogen receptors (ER) and microarray analysis of lumiestrone-exposed goldfish to show that lumiestrone, a major E1 photoproduct, is estrogenic.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, according to the structure of E1 and the similar characteristics of UV and mass spectra, the isomeric structure of P1 is quite difficult to put forward and the assumption that P1 corresponds to a photo enol structure should be further investigated. Trudeau et al [26] researched the UV-B radiation on the photodegradation potential of estrone; UV-B-mediated degradation leads to the photoproduction of lumiestrone (Figure 9b), a little-known 13α-epimer form of estrone. (DOC), a unique photoproduct (P1, Figure 9a) was observed at a retention time higher than E1, by direct HPLC analyses.…”
Section: Identification Of E1 Photoproductsmentioning
confidence: 99%
“…Overall, it is concluded that estrone and estriol should not be considered as compounds of concern for priority follow-up. However, a photolysis product of estrone, lumiestrone, has been shown to be estrogenic and persistent (75) and therefore warrants further consideration.…”
Section: Risk Assessment Using Predicted Exposure Concentrationsmentioning
confidence: 99%